Antibacterial Activity of Extracts Derived from the Unicellular Green Algae, Chlorella spp. - Choochote*, Weena; Kruawanishtham, Pongtorn; Phumprasert, Phansa; Janvechsakda, Wittawas (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Antibacterial substances from five strains of unicellular green algae, Chlorella spp., were extracted in water: methanol : chloroform (1 : 2 : 1, v/v). The highest yield of crude algal extract (0.24 g/g dry weight) was obtained from Chlorella spp. A. 0505. Various concentrations of the extracts were tested against 6 genera of bacteria for antibacterial activity by the disc diffusion method. It was found that the crude algal extracts (4 mg/disc) from Chlorella vulgaris TISTR 8580 strongly inhibited the growth of Staphylococcus aureus and Streptococcus pyogenes. Moreover, the extracts from Chlorella spp. A. 0505 and Chlorella vulgaris TISTR 8261 have been found to effectively inhibit the growth of Pseudomonas aeruginosa and Bacillus subtilis, respectively. Keywords: Antibacterial activity, unicellular green algae, Chlorella spp. Corresponding author: E-mail: Keweena@kmitl.ac.th